Association of Serum Creatinine and NT-ProBNP Levels with the Length of Hospital Stay in Patients with Decompensated Heart Failure - Poudel, Samir Kumar; Sherpa, Kunjang; Gautam, Binayak; Bogati, Prakash; Ghimire, Nirmal; Lamsal, Sudip; Mishra, Deepak Kumar; Koirala, Prabha Chapagain; Poudel, Lata Gautam (Journal of National Heart and Lung Society Nepal, 2024)
Background:Despite the increasing arsenals in the basket of heart failure armamentarium, the management of acute decompensated heart failure still remains a partly resolved mystery with high morbidity and mortality. This study seeking correlation between serum NT-ProBNP, and serum creatinine at presentation in acute decompensated heart failure (ADHF) patients with the length of hospital stay (LOS) will give an idea about prioritizing ADHF patients for further management and proper downstream resource utilization. Methods: This was a hospital-based prospective observational study conducted at National Academy of Medical Sciences, Bir Hospital, Kathmandu, Nepal. The study duration was from August 2023 to July 2024. Seventy-three consecutive patients above 18 years of age with ADHF were enrolled in the study. Patients underwent NT=ProBNP and serum creatinine tests from the routine lab within 24 hours of presentation to emergency department. The correlation between LOS and NT-ProBNP/ serum creatinine was assessed by Spearman correlation. Results: Out of the 73 patients, females were higher in number (56.16%). The mean age of the population was (64.68 + 16.19) years and the mean hospital stay was (9.89 + 4.3) days. There was a moderately strong correlation between LOS and serum NT-ProBNP level (r = 0.419, p = 0.027). However, the correlation between LOS and serum creatinine was weak (r = 0.245, p = 0.037). Conclusion: Serum NT-ProBNP taken within first 24-hours of admission in ADHF patients has moderately strong correlation with LOS in hospital; however, serum creatinine is a weak predictor of LOS in this cohort of patients.